2015
DOI: 10.1177/1060028014559244
|View full text |Cite
|
Sign up to set email alerts
|

Use of Proton Pump Inhibitors in the Management of Gastroesophageal Varices

Abstract: The best available evidence supports the use of short-course (10 days) PPI post-endoscopic variceal ligation to reduce ulcer size if ulcer healing is a concern. Practices such as high-dose infusion and prolonged use should be discouraged until evidence of benefit becomes available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 46 publications
0
43
0
4
Order By: Relevance
“…The best available evidence supports the short-term use (maximum 10 days) of PPIs to reduce ulcer size, provided spontaneous ulcer healing is a concern. Practices such as high dose infusion and prolonged use should be discouraged until evidence of benefit becomes available [353]. …”
Section: Resultsmentioning
confidence: 99%
“…The best available evidence supports the short-term use (maximum 10 days) of PPIs to reduce ulcer size, provided spontaneous ulcer healing is a concern. Practices such as high dose infusion and prolonged use should be discouraged until evidence of benefit becomes available [353]. …”
Section: Resultsmentioning
confidence: 99%
“…[2931]. In a systemic review conducted by Lo et al [21], the best evidence for PPIs was suggested to still be lacking, and the use of a short-course (10 days) of PPIs to reduce ulcer size whenever ulcer healing was a concern was supported. Lodato et al further suggested that the use of PPI with regard to the prevention and treatment of esophageal complications after banding or sclerotherapy of esophageal varices may be more of a tradition rather than an evidence-based practice, due to the lack of convincing evidence [32].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, one may argue that the clinical importance of such findings is not known given the self-limiting nature of esophageal ulcers. In addition, accumulating data suggest that PPIs have other important negative effects on events in cirrhosis, such as spontaneous bacterial peritonitis and encephalopathy [1921]. Thus, the use of PPI in acute EV bleeding and post-EVL care in Taiwan has been restricted by the National Health Insurance.…”
Section: Introductionmentioning
confidence: 99%
“…ALP is a phenotypic marker for osteoblasts, which may directly represent the activities and functional status of osteoblast cells (15). During early stages of osteogenesis, the activity of ALP is marked.…”
Section: Discussionmentioning
confidence: 99%